Pengaruh Strategi Pembelajaran PQ4R (Preview, Question, Read, Reflect, Recite, Review) Terhadap Hasil Belajar Ilmu Pengetahuan Alam Terpadu Siswa Madrasah Tsanawiyah : The Influence of PQ4R Learning Strategies (Preview, Question, Read, Reflect, Recite, Review) on Integrated Natural Sciences Learning Outcomes Madrasah Tsanawiyah students - Try Susanti; Rizki Khairati; Badariah Badariah (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2019)
The purpose of this study was to determine the effect of the PQ4R Learning strategy (Preview, Question, Read, Reflect, Recite, Review) on the learning outcomes of Integrated Science in Islamic Education in Biology learning. This research is a quasi-experimental study using the Posttest-Only Control Design design while data collection is done using a test instrument. The sample of the study was class VIII C (experimental class) totaling 28 students and class VIII D (control class) totaling 28 students. The research data obtained the highest score in the experimental class was 92 and the lowest score was 44 with an average of 72, while in the control class the highest score was 80 and the lowest score was 40 with an average of 63.57. Based on the calculation using the t test obtained thitung = 2.77 and at a significant level of 5% obtained ttable = 2.01 and a significance level of 1% t table = 2.68 thus 2.01 <2.77> 2.68. So that Ha is accepted, meaning that there is a significant influence on the results of Integrated Science learning of students who use the PQ4R learning strategy (Preview, Question, Read, Reflect, Recite, Review) in the Madrasah Tsanawiyah. Keyword: Student learning outcomes, PQ4R learning strategy (Preview, Question, Read, Reflect, Recite,Review) Abstrak. Tujuan Penelitian ini adaah untuk mengetahui pengaruh strategi Pembelajaran PQ4R (Preview, Question, Read, Reflect, Recite, Review) terhadap hasil belajar IPA Terpadu di Madrasah Tsanawiyah pada pembelajaran Biologi. Penelitian ini merupakan penelitian quasi eksperimen dengan menggunakan desain Posttest-Only Control Design sedangkan pengumpulan data dilakukan dengan menggunakan instrumen tes. Sampel penelitian adalah siswa kelas VIII C (kelas eksperimen) berjumlah 28 orang siswa dan siswa kelas VIII D (kelas kontrol) berjumlah 28 orang siswa. Data hasil penelitian di peroleh skor tertinggi di kelas eksperimen adalah 92 dan skor terendah 44 dengan rata-rata 72, sedangkan pada kelas kontrol diperoleh skor tertinggi 80 dan skor terendah 40 dengan rata-rata 63,57. Berdasarkan perhitungan menggunakan uji t diperoleh thitung= 2,77 dan pada taraf signifikan 5% diperoleh ttabel = 2,01 dan taraf signifikansi 1% ttabel= 2,68 dengan demikian Sehingga Ha diterima, artinya bahwa terdapat pengaruh yang signifikan terhadap hasil belajar IPA Terpadu siswa yang menggunakan strategi pembelajaran PQ4R (Preview, Question, Read, Reflect, Recite, Review) di Madrasah Tsanawiyah. Kata kunci: Hasil belajar siswa, startegi pembelajaran PQ4R (Preview, Question, Read, Reflect, Recite, Review)